People, mice and livestock. The story of African trypanosomiasis - International Livestock Research Institute (Doyle Foundation, 2006)
This Doyle Foundation meeting on 'People, mice and livestock.: the story of African trypanosomiasis' was conducted to examine the current status of trypanosomosis in Africa and future research opportunities; and to look at the opportunities for use in the new biosciences platform which has been developed at ILRI, Nairobi campus., as well as research collaboratives through out Africa particularly eastern and central Africa regions with a number of notes which are developing in other African countries. This meeting is formulated with reference to two questions, Why Tryps; and Why Here. The Other is divided in four sections. The first and last sections - introduction and conclusion are presented by Gabrielle Parsley of Doyle Foundation. The other sections are interviews and debate. The interview has seven parts. Seven scientists from different institutes were interviewed by six different interviewers.